2011
DOI: 10.4331/wjbc.v2.i10.232
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of autophagy and apoptosis: Recent developments in breast cancer cells

Abstract: Autophagy, the pathway whereby cell components are degraded by lysosomes, is involved in the cell response to environmental stresses, such as nutrient deprivation, hypoxia or exposition to chemotherapeutic agents. Under these conditions, which are reminiscent of certain phases of tumor development, autophagy either promotes cell survival or induces cell death. This strengthens the possibility that autophagy could be an important target in cancer therapy, as has been proposed. Here, we describe the regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…Some studies suggest that autophagy can promote cell death in breast cancer with a sufficient stimulus or when apoptosis is inhibited. In contrast, autophagy may be triggered by cytotoxic agents to prevent cell death and inhibitors of autophagy enhance cytotoxicity and increase cell death . Our former study confirmed that blocking EPI‐induced autophagy increased caspase‐9‐dependent intrinsic apoptosis and promoted cell death .…”
Section: Discussionsupporting
confidence: 68%
“…Some studies suggest that autophagy can promote cell death in breast cancer with a sufficient stimulus or when apoptosis is inhibited. In contrast, autophagy may be triggered by cytotoxic agents to prevent cell death and inhibitors of autophagy enhance cytotoxicity and increase cell death . Our former study confirmed that blocking EPI‐induced autophagy increased caspase‐9‐dependent intrinsic apoptosis and promoted cell death .…”
Section: Discussionsupporting
confidence: 68%
“…Stress conditions induce cancer cells to autophagy and it enables cancer cells to survive by providing biosynthetic precursors, maintaining energy production, and clearing injured cell components (22). Clearly, autophagy plays an important role in tumor cell survival under extreme stress, thus inhibition of autophagy may become a novel therapeutic strategy for cancer treatment (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The human MCF7 breast cancer cell line was used initially because autophagy has been well characterized in this cell line (45). In these investigations, Dp44mT was used at low concentrations of up to 5 M because of its high membrane permeability and marked iron chelation efficacy (20).…”
Section: Dp44mt and Dfo Increase Lc3-ii Levels And Autophagosome Formmentioning
confidence: 99%